Directed organization of gold nanoclusters on silver nanowires: a step forward in heterostructure assembly - Sharma, J.; Vivek, J. P.; Vijayamohanan, K. P.; Singh, P.; Dharmadhikari, C. V. (Applied Physics Letters, 2006)
We investigate the directed assembly of tridecylamine protected gold nanoclusters of 4-5 nm size on functionalized silver nanowires of 55-60 nm diameter and the electron transfer behavior of this integrated structure using transmission electron microscopy, non-contact atomic force microscopy, and scanning tunneling microscopy/spectroscopy. Linear I-V for bare silver nanowire suggests metallic behavior but high tunnel resistance indicates presence of insulating layer on the surface. Identical I-Vs obtained for isolated gold nanoparticle and heterostructure suggests that electron transport across nanowires in the latter is governed by gold nanoparticles in contrast to expected ballistic or diffusive transport along their length.(c) 2006 American Institute of Physics.

Biosynthesis of antinutritional alkaloids in solanaceous crops is mediated by clustered genes - Itkin, M.; Heinig, U.; Tzfadia, O.; Bhide, Amey J.; Shinde, B.; Cardenas, Pablo D.; Bocobza, S. E.; Unger, T.; Malitsky, Sergey; Finkers, R.; Tikunov, Y.; Bovy, A.; et al. (Science, 2013)
Steroidal glycoalkaloids (SGAs) such as alpha-solanine found in solanaceous food plants-as, for example, potato-are antinutritional factors for humans. Comparative coexpression analysis between tomato and potato coupled with chemical profiling revealed an array of 10 genes that partake in SGA biosynthesis. We discovered that six of them exist as a cluster on chromosome 7, whereas an additional two are adjacent in a duplicated genomic region on chromosome 12. Following systematic functional analysis, we suggest a revised SGA biosynthetic pathway starting from cholesterol up to the tetrasaccharide moiety linked to the tomato SGA aglycone. Silencing GLYCOALKALOID METABOLISM 4 prevented accumulation of SGAs in potato tubers and tomato fruit. This may provide a means for removal of unsafe, antinutritional substances present in these widely used food crops.